Effects of Brand Equity on Evaluating Consumers’ Attitude towards Brand Extension of Iranian Tire Product - d faiz; m deghanisoltani (کاوش‌های مدیریت بازرگانی, 2014)
Brand extension has become a famous strategy for many companies since many years ago. Its success depends on acceptance and evaluation of consumers about brand extension. In this study, according to the crucial role of the brand, we analyze the role of brand equity on Evaluating Consumers’ Attitude towards Brand Extension of Barez tire in the city of Kerman. The population in this study is the consumers of Barez tire in Kerman and the sample size is 171 patients. To obtain this population, we use random sampling method and an infinite population formula. The data collection tool in this study is a standard questionnaire and for reliability of this questionnaire, Cronbach’s alpha coefficient is used. By the use of structural equation modeling (SEM), we examine the causal relationship between the brand equity and Evaluating Consumers’ Attitude towards Brand Extension. Besides, the fitness of Aaker model has been evaluated in the industry. The results show Brand Equity significantly affects the evaluating of consumers’ attitudes toward brand extension. However, Brand awareness and Brand Loyalty are more effective than other factors.